2012
DOI: 10.1002/adfm.201201065
|View full text |Cite
|
Sign up to set email alerts
|

Co‐Assembled and Microfabricated Bioactive Membranes

Abstract: The fabrication of hierarchical and bioactive self‐supporting membranes, which integrate physical and biomolecular elements, using a single‐step process that combines molecular self‐assembly with soft lithography is reported. A positively charged multidomain peptide (with or without the cell‐adhesive sequence arginine‐glycine‐aspartic acid‐serine (RGDS)) self‐assembles with hyaluronic acid (HA), an anionic biopolymer. Optimization of the assembling conditions enables the realization of membranes with well‐cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 45 publications
3
55
0
Order By: Relevance
“…Zeta potential ( ) measurements confirmed that both components xanthan and chitosan oligomers have opposite charge and hence, they are able to co-assemble by electrostatic interactions. These type of interactions have been shown essential to drive the self-assembly of interfacial systems [2,5,30,31].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Zeta potential ( ) measurements confirmed that both components xanthan and chitosan oligomers have opposite charge and hence, they are able to co-assemble by electrostatic interactions. These type of interactions have been shown essential to drive the self-assembly of interfacial systems [2,5,30,31].…”
Section: Resultsmentioning
confidence: 99%
“…The structures were fixed in 2.5% (v/v) glutaraldehyde (in phosphate buffer solution (PBS), pH 7.4) for 1 h. The samples were then dehydrated in a graded ethanol series (50, 70, 90, 96 and 100%) followed by immersion in hexamethyldisilazane (HMDS) [2]. For SEM, the specimens were mounted on aluminum stubs and sputtercoated with gold prior to the visualization on a scanning electron microscope Quanta FEG 3D SEM.…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
See 1 more Smart Citation
“…29 Mata's group described hybrid multifunctional nanofibrous membranes based on electrostatic interactions between the co-assembled cationic peptide and anionic biopolymer (HA). 30 It is clear from these examples that co-assembly between biopolymers and selfassembling peptides can have dramatic effects on materials properties and consequent function. Here, we combine these two areas and investigate whether dynamic peptide-polymer assembly can be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of external inputs include mechanical forces, such as shear effects 5 , magnetic 6 and electric 7 fields, thermal gradients 8 and chemically 9 or topographically 10 patterned substrates. Although the concept of DSA still remains ambiguous, templated self-assembly (TSA) can be considered as a kind of DSA, in which a prefabricated ''template'' orients and directs the assembling components.…”
Section: Introductionmentioning
confidence: 99%